Transdermal Delivery of Snakehead Fish (Ophiocephalus striatus) Nanoemulgel Containing Hydrophobic Powder for Burn Wound - Robert Tungadi; Widy Susanty; Prisca Wicita; Elvira Pido (Tabriz University of Medical Sciences, 2018)
Background: The aim of the present study was to characterize and evaluate the nanoemulgel (NEG) of snakehead fish powder (SFP), as a transdermal delivery system for poorly water soluble drug, in order to conquer the inconveniences related to its oral conveyance. Methods: Diverse nanoemulsion components (oil, surfactant, and co-surfactant) were chosen based on solvency and emulsification capacity. SFP loaded nanoemulsion which tested by stress-stability testing was carried out for all formulations and those that passed these tests were characterized for mean droplet size, polydispersity index (PDI), zeta potential, pH, viscosity, and transmittance. After that, this was continued by permeation studies using snake skin in vitro and rabbit skin in vivo studies i.e. skin irritation study and the effectiveness test. Results: Mean droplet size and zeta potential of the optimized nanoemulsion (NE4) were found to be 98.6 ± 0.93 nm (polydispersity index, PDI = 0.1 ± 0.20) and -57.5 ± 0.3 mV respectively. Optimized nanoemulsion was converted into nanoemulgel with 1.5% w/v of gelling agent (HPMC) and evaluated for pH, viscosity, spreadability, and extrudability measurement. Ex vivo transdermal permeation value for SFP through snake skin as membrane from NEG1, NEG2, NEG3 and marketed SFP cream showed results of 55.65 ± 0.93%, 56.14 ± 0.70%, 66.75 ± 1.03% and 49.80 ± 3.42% respectively in 3 hours. Moreover, all the treatment group did not show skin irritation of each group. The effect of burn wound healing of NEG3 showed a significant (P<0.05) on the measurement of wound area compared to marketed cream. Conclusion: The novel NEG of SFP was successfully formulated for transdermal application based on the results of evaluations and stability tests on accelerating burn wound healing.